(untitled) (Bangladesh Journal of Medicine, 2024)
Background: Dengue is an important tropical infection caused by Dengue virus and its epidemics are becoming more frequent over the time. Gastrointestinal (GI) manifestation is one of the most common manifestations and mostly missed due to lack of awareness and knowledge. This study was conducted to find out the gastrointestinal manifestations, laboratory parameters and its correlation with the severity of dengue fever. Methods: It was a cross-sectional observational study, conducted on 100 serologically confirmed dengue virus infected patients admitted in DNCC Dedicated Covid-19 Hospital. Patients were examined clinically, and laboratory data was collected in respect of GI manifestations. Statistical analysis was done using SPSS software version 25. Results: The study participants were 100 consecutive cases of dengue syndrome, out of which 38% cases were dengue fever (DF), 12% were Dengue haemorrhagic fever (DHF), 22% were Dengue Shock syndrome (DSS) and 28% were Dengue expanded syndrome (DES). Mean age was 29.66 ± 19.69 years and age range were from 03 to 85 years, 62% were males and 38% were females, male to female ratio was1.6:1, and 44% patients were from Dhaka city. Gastrointestinal manifestations were anorexia 92%, nausea 90% & abdominal pain and vomiting were 84% followed by diarrhoea 56%. GI bleeding manifesting were 38%, among them, hematemesis, melena and gum bleeding were found 14%, 26% and 16% respectively. Others manifestations like ascites, hepatomegaly, acalculous cholecystitis and jaundice were found 52%, 26%, 42% and 10% respectively. Of these, GI manifestations diarrhoea correlated with severity of Dengue fever. Conclusion: Gastrointestinal manifestations are very common in Dengue fever. Atypical Gastrointestinal manifestations should be handled very cautiously. Bangladesh J Medicine 2025; 36: 37-42